2009
DOI: 10.1016/j.adolescence.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes and gender differences in adolescents' perceptions of friendships

Abstract: This five-wave study aims to investigate the development of adolescents' perceptions of support, negative interaction, and power in best friendships from ages 12 to 20 years. Furthermore, gender differences and linkages between the three dimensions are explored. A total of 593 early adolescents (53.6% boys) and 337 middle adolescents (43.3% boys) participated. A multigroup multivariate accelerated growth curve showed an increase of support for both boys and girls. Negative interaction was found to temporarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
101
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 50 publications
7
101
0
5
Order By: Relevance
“…Theoretical and empirical work suggests that as adolescents become more autonomous from parents, their friendships become increasingly intimate and offer an important source of social support (De Goede, Branje, & Meeusy, 2009;Furman & Buhrmester, 1992;Sullivan, 1953). There is also evidence that stress and coping responses vary across development in terms of the types of stressors adolescents experience as stressful, the competencies and behaviors adolescents can bring to bear to cope with stress, and the flexibility with which they can draw on their coping repertoire.…”
mentioning
confidence: 99%
“…Theoretical and empirical work suggests that as adolescents become more autonomous from parents, their friendships become increasingly intimate and offer an important source of social support (De Goede, Branje, & Meeusy, 2009;Furman & Buhrmester, 1992;Sullivan, 1953). There is also evidence that stress and coping responses vary across development in terms of the types of stressors adolescents experience as stressful, the competencies and behaviors adolescents can bring to bear to cope with stress, and the flexibility with which they can draw on their coping repertoire.…”
mentioning
confidence: 99%
“…Experiencing a loss could lead to growth and maturity, but may also interfere with normal developmental tasks and impede function (Doka, 2000;Neimeyer, Laurie, Mehta, Hardison, & Currier, 2008 ). Young girls have a closer relationship with their friends than boys do, with higher levels of both intimacy and peer support (Coleman, 2011;De Goede, Branje, & Meeus, 2009;Malone, 2012;Markiewicz, Lawford, Doyle, & Haggart, 2006), predicting stronger grief reactions in girls.…”
mentioning
confidence: 99%
“…Moreover, girls tend to be more supportive and focus on equality than boys. This is because they are generally two years ahead of boys in intellectual and social-cognitive functioning (De Goede et al, 2009). On the contrary, females are hypothesized to be more willing and tend to share more information on intimate topics with their best friends than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, girls have more self-disclosure, empathy, interdependence, and need for nurturance in an intimate friendship, whereas boys normally search for companionship, competition, control, and conflict in larger friendship groups. Differences in how relationships are perceived or evaluated could result in differences in friendship quality, and males and females have different views of friendship (Bae, 2003;De Goede, Branje & Meeus, 2009;Rodebaugh, Fernandez & Levinson, 2012). Previous studies have indicated that there is a slightly significant difference in underlying construct of friendship quality between males and females.…”
Section: The Role Of Friendship Quality In Individuals' Lifementioning
confidence: 99%
See 1 more Smart Citation